A Development of Communicative Language Teaching Using Edmodo for Fostering Students’ Skills and Motivation - Eka Uliyanti Putri Br. Bangun (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. The goals of this research were to establish a communicative language teaching (CLT) approach that used Edmodo as an instructional platform in language learning and to evaluate the technique's efficacy in an English course in terms of writing competence, motivation, and attitude. The researcher also gave alternative ways to support writing tasks with Edmodo through artificial intelligence (computational linguistic or Grammarly). The participants were divided into two groups at random: experimental and control. The total of the sample in this research was 40 students. The subjects in this research were junior high school students in the first grade. The students in the experimental group were instructed by a communicative language teaching approach supported by using online learning (Edmodo); while, students in the control group were implemented regular teaching instruction. The findings indicated that communicative language teaching could significantly improve the students' writing skills compared with those who were not exposed to such a method. Specifically, students who were exposed to Edmodo in Communicative language teaching could achieve a higher score and showed a good motivation to learn English compared with those who were not exposed to the communicative language teaching method. Using Edmodo supported by artificial intelligence tools became one of the innovative ways to conduct more effective teaching in English language teaching.Keywords: Communicative language teaching, EdmodoAbstrak. Tujuan dari penelituan ini adalah untuk mengembangkan communicative language teachinf (CLT) dalam penggunaan Edmodo sebagai alat pembelajaran dalam belajar bahasa dan menguji keefektifan dari metode yang diimplementasikan di pelajaran bahasa Inggris terkait dalam kemampuan menulis, motivasi dan sikap. Peneliti juga memberikan cara alternatif untuk mendukung tugas menulis dengan Edmodo melalui kecerdasan buatan (commputational linguistic dan grammarly. Siswa dibagi 2 kelompok: grup eksperimental dan grup kontrol. Jumlah dari sampel di penelitian sebanyak 40 siswa. Sampel penelitian ini adalah siswa kelas I SMP. Siswa pada kelompok eksperimen menerapkan metode pengajaran bahasa komunikatif yang didukung dengan pembelajaran online Edmodo; sedangkan, siswa dalam kelompok kontrol diimplementasikan instruksi pengajaran reguler. Temuan menunjukkan bahwa siswa diajarkan pengajaran bahasa komunikatif lebih efektif daripada pengajaran pengajaran biasa. Temuan menunjukkan bahwa pengajaran bahasa komunikatif dapat secara signifikan meningkatkan keterampilan menulis siswa dibandingkan dengan mereka yang tidak terkena metode tersebut. Secara khusus, siswa yang di ajarkan Edmodo dalam pengajaran bahasa Komunikatif dapat mencapai skor yang lebih tinggi dan menunjukkan motivasi yang baik untuk belajar bahasa Inggris dibandingkan dengan mereka yang tidak diberikan metode pengajaran bahasa komunikatif. Menggunakan Edmodo dengan didukung oleh alat kecerdasan buatan menjadi salah satu cara inovatif untuk melakukan pengajaran yang lebih efektif dalam pengajaran bahasa Inggris. Kata kunci: pengajaran bahasa komunikatif, Edmodo